ELEMENTARY SCHOOL TEACHERS’ PERSPECTIVES ON USING CHATGPT IN EDUCATION - Maxie Liando; Junita Christi Makawawa (SOSIOEDUKASI, 2025)
The rapid development of Artificial Intelligence (AI) technology has introduced new opportunities in education, one of which is the use of ChatGPT. This application is believed to support teachers in designing lesson plans, developing test items, and providing more creative variations in the learning process. However, its utilization at the elementary school level still raises concerns, particularly regarding teachers’ readiness, infrastructural limitations, and ethical considerations. Therefore, this study aims to explore elementary school teachers’ perspectives on the use of ChatGPT, with a particular focus on Tomohon City. The objective of this research is to describe the benefits, challenges, and expectations of teachers in employing ChatGPT as part of the teaching and learning process. A descriptive qualitative method was applied, involving all elementary school teachers in Tomohon City, totaling 192 teachers from 32 schools. Data were collected through open-ended questionnaires, in-depth interviews, and documentation, and analyzed using thematic analysis with the interactive model of Miles, Huberman, and Saldaña. The findings indicate that most teachers hold a positive perception of ChatGPT, especially in enhancing the efficiency of lesson plan preparation and the development of instructional materials. Nevertheless, teachers still face challenges such as limited digital literacy, inadequate internet access, and concerns regarding information accuracy and ethical use. Teachers also emphasize the importance of digital literacy training and ethical guidelines to ensure more effective utilization of ChatGPT. These findings contribute to the academic discourse by broadening the understanding of generative AI adoption in elementary education while highlighting the need for policy support, infrastructure improvement, and teacher capacity-building.